Exploring the experiences and perceptions of students in a graduate entry nursing programme: A qualitative meta-synthesis. (December 2021) - Jarden, Rebecca J.; Jones, Virginia; McClunie-Trust, Patricia; Winnington, Rhona; Merrick, Eamon; Shannon, Kay; Turner, Rosemary; Donaldson, Andrea E.; Macdiarmid, Rachel
Abstract: Background: Students commencing graduate entry fast-tracked nursing programmes leading to registration are highly motivated and characterised by rich life experiences. Given their unique motivations and characteristics, gaining insight into their experiences of graduate entry programmes will inform strategic directions in education. Objective: To synthesise graduate entry nursing students' self-reported experiences and perceptions of their accelerated programme. Design: Qualitative meta-synthesis. Data sources: Databases included Cumulative Index of Nursing and Allied Health Literature, Emcare, Education Resources Information Centre, Medical Literature Analysis and Retrieval System Online, Psychological Information and Scopus. Qualitative studies published in English and reporting primary data analysis including experiences and perceptions of graduate entry nursing students were considered. Review methods: Qualitative studies were systematically identified and critically appraised. The meta-synthesis used an open card sort technique to organise data into a matrix of graduate entry nursing students' experiences and perceptions. Results: Fourteen studies were included. The analysis revealed three primary themes: what I bring and what I come with, developing a sense of self and nursing self, and what I need. Within these themes we found potential enablers of student success in learning; space, working together, and balancing work and life and learning to bridge two worlds. Students reflected on the benefits of academic support and shared their experiences of learning in clinical placement. In addition, students acknowledged the importance of clinical educators and preceptors who provided bridging that was further scaffolded by simulated learning experiences. Conclusions: Findings indicate graduate entry nursing students have important needs and expectations of support in transition. The experiences and perceptions of graduate entry nursing students differentiated into what students arrived with, what support they need in their journey to become a nurse, alongside their experience of building a sense of self and their nursing self. Systematic review registration number: CRD42020220201. Highlights: Review found enablers of student success in learning to bridge the clinical and academic worlds Enablers were space, working together, and balancing work, life, and learning Educators and preceptors provided bridging, scaffolded by simulated learning Themes were what I bring and what I come with, developing nursing self, and what I need Opportunity to recognise and capitalise on students' strengths and explore supports